Awareness of Enhancing Pragmatic Competence Via Movies and Effectiveness of Teaching Conversational Implicature Using Films - Alharbi, Wejdan Ammash; Shet, Jayashree Premkumar (Journal of Social Sciences and Management Studies, 2023)
Rapid advancements in language technologies have created enormous opportunities for teaching and learning a second language. Using films as an aid is the best teaching method available to support students and also to enable them to study in a purposeful manner with fun and entertainment. Films are one of the infrequently used multimedia technologies. In this light this study focuses on the value of understanding the meaning behind the individual’s utterances, the complexity of speech in a language, and the knowledge of teaching and learning conversational implicature through movies. This research investigates the perception of implicature via a questionnaire to EFL learners in Saudi Arabia, where, as in East Asian countries, English is acquired as a foreign language. There were 441 respondents. Also this descriptive qualitative study lists the floutings of Paul Grice’s Cooperative Principle (1975) and the implicature in Plane Movie. In real life in queer situations if asked a personal question, to which they are reluctant to reply, 66.5% of the respondents chose to opt for flouting Maxim of Relevance, whereas 32.4% opted for flouting to the quality maxim Their responses to the question of whether language learning can be done through regular classroom studies ormovies, or both, came out in favor of both. In contrast to the 22.1% who said they could only acquire the language through studies and the 23.2% who said they could only learn it from movies, 54.7% of respondents said they could learn the language in both situations. The study suggests that in order to teach pragmatic concepts like conversational implicature, English curriculum should also contain visual aids like movies, and language teachers should use them while assigning homework or assignments. This study’s findings has significant repercussions that might be advantageous to EFL/ESL students, teachers, and curriculum designers.